Analisis Faktor-faktor yang Mempengaruhi Produksi Jagung di Kecamatan Batu Ampar Kabupaten Tanah Laut - Adi Budiono; Kamiliah Wilda; Nuri Dewi Yanti (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The study is purposed to identify maize farming technique, to analize factors influence maize yield, and to identify farmer’s problem in Kecamatan Batu Ampar, Kabupaten Tanah Laut. Cobb-Douglas production function was used to analyze the effects of inputs on maize yield, elasticities and return to scale. The study summarize that land area, labor, seed, organic fertilizer, N fertilizer, Phonska efrtilizer and herbicide simultaneously affect the yield on 95% confidence level. Partially, organic and Phonska fertilizer which are not significantly affect the yield. Furthermore, only land area, labor, phonska and organic fertilizer which has positive elasticity. Maize farming in Kecamatan Batu Ampar is on constant return to scale.